2006
DOI: 10.1016/j.vph.2006.08.144
|View full text |Cite
|
Sign up to set email alerts
|

Laminar shear stress inhibits cathepsin L activity in endothelial cells

Abstract: Objective-The cysteine proteases, cathepsins, have been implicated in vascular remodeling and atherosclerosis, processes known to be regulated by shear stress. It is not known, however, whether shear regulates cathepsins. We examined the hypothesis that shear stress regulates cathepsin activity in endothelial cells. Methods and Results-Mouse aortic endothelial cells (MAECs) exposed to atheroprotective, unidirectional laminar shear (LS) degraded significantly less BODIPY-labeled elastin and gelatin in compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 17 publications
2
29
0
3
Order By: Relevance
“…The associated increase in collagen content at 15% and 20% stretch led us to further speculate that cathepsin L is a key enzyme involved in normal collagen turnover in valve cusps, wherein its downregulation under 15% and 20% stretch resulted in increased collagen content. Previous studies in our laboratory showed that cathepsin L was downregulated by altered levels of cyclic pressure (25) and laminar shear stress (23,24), further lending strength to this speculation.…”
Section: Discussionmentioning
confidence: 52%
“…The associated increase in collagen content at 15% and 20% stretch led us to further speculate that cathepsin L is a key enzyme involved in normal collagen turnover in valve cusps, wherein its downregulation under 15% and 20% stretch resulted in increased collagen content. Previous studies in our laboratory showed that cathepsin L was downregulated by altered levels of cyclic pressure (25) and laminar shear stress (23,24), further lending strength to this speculation.…”
Section: Discussionmentioning
confidence: 52%
“…Endothelial cells have been found to possess elastase-like activity (36)(37)(38)(39). In addition, Platt et al used fluorescently labeled gelatin and elastin as matrix substrates to demonstrate that live endothelial cells exhibit varying degrees of gelatinase and elastase activities depending upon the degree of shear stress (62). We found that TLR4-deficient endothelial cells and WT lung endothelial cells, in which TLR4 expression was silenced, exhibited exaggerated levels of elastolytic activity that was reversed in the presence of Nox3 siRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Because it is well known that microarray results obtained by different laboratories significantly vary, 40 we first compared our mouse array result obtained using the mouse Illumina BeadChip array with that of HUVEC microarray using the human Illumina BeadChip array, as we recently reported (GSE20739). As shown in supplemental (12,24, and 48 hours) after ligation were collected. Differentially expressed genes were selected for quantitative PCR analyses based on 48-hour microarray results.…”
Section: Comparison Of Microarray Data Between the In Vivo Mouse Caromentioning
confidence: 99%
“…We selected 46 genes (10 up-regulated, 30 downregulated genes plus 6 additional genes of interests, although they were not significantly changed at 48 hours after ligation) and tested by quantitative PCR assay with either the TaqMan (28 genes, supplemental Table 3) or SYBR Green (18 genes, supplemental Table 4) method using total endothelial RNAs obtained from LCAs or RCAs collected at 3 different time points (12,24, and 48 hours after ligation). These RNAs used for quantitative PCR validation were entirely independent from those used in the microarray study.…”
Section: Validation Of Mechanosensitive Genes By Quantitative Pcrmentioning
confidence: 99%
See 1 more Smart Citation